2012
DOI: 10.1172/jci62848
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 in the ventromedial hypothalamus regulates energy balance

Abstract: The transcription factor FOXO1 plays a central role in metabolic homeostasis by regulating leptin and insulin activity in many cell types, including neurons. However, the neurons mediating these effects and the identity of the molecular targets through which FOXO1 regulates metabolism remain to be defined. Here, we show that the ventral medial nucleus of the hypothalamus (VMH) is a key site of FOXO1 action. We found that mice lacking FOXO1 in steroidogenic factor 1 (SF-1) neurons of the VMH are lean due to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 50 publications
2
113
0
Order By: Relevance
“…137 SF1 neurons seem to be negatively modulated by the CB1 as its deletion in SF1 neurons reduces adiposity in mice. 142 SF1 is a direct transcriptional target of FOXO1 143 and mice with a selective deletion of Foxo1 in SF1-expressing neurons have reduced adiposity and increased energy expenditure. 143 Moreover, a subset of SF1 neurons expresses brain-derived neurotrophic factor, whose selective deletion in the VMH and adjacent DMH results in obesity.…”
Section: Sns Control Of Bat Thermogenesismentioning
confidence: 99%
“…137 SF1 neurons seem to be negatively modulated by the CB1 as its deletion in SF1 neurons reduces adiposity in mice. 142 SF1 is a direct transcriptional target of FOXO1 143 and mice with a selective deletion of Foxo1 in SF1-expressing neurons have reduced adiposity and increased energy expenditure. 143 Moreover, a subset of SF1 neurons expresses brain-derived neurotrophic factor, whose selective deletion in the VMH and adjacent DMH results in obesity.…”
Section: Sns Control Of Bat Thermogenesismentioning
confidence: 99%
“…The concept that Foxo1 has pro-hyperglycemic properties is established based on a series of works that involve manipulations of the endogenous level and activity of Foxo1. Genetic ablation of Foxo1 in hypothalamus is known to enhance glucose uptake in gastrocnemius muscle [33]. Recent efforts have demonstrated that reducing the endogenous level of Foxo1 by knockdown approach abolished the elevation of MAPK phosphatase-3 (MKP-3), a factor known to induce transcriptional activation of gluconeogenic phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase complex (G6pase) in dexamethasone-treated hepatoma cells [34,35].…”
Section: Foxo1 As a Negative Regulator Of Glucose Utilization In The mentioning
confidence: 99%
“…Sections containing the VMH (bregma -1.20 to -2.22 mm) were analyzed by immunohistochemistry, as described (57,58). Immunostaining was performed using rabbit polyclonal pAKT (S473 D9E; 1:50; Cell Signaling Technology) and pFOXO1 (#28280, 1:50; Cell Signaling Technology) antibodies, based on previous publications (52,59). Primary antibodies were detected by using anti-rabbit IgG secondary antibodies, VECTA-STAIN Elite plus ABC kits, and NovaRed kits (Vector Laboratories Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the obesity and decreased EE phenotype in Sf1-Ptpn1 -/-mice is consistent with several models in which genes encoding components of the insulin-signaling pathway have been deleted in SF-1 neurons. For example, deletion of Insr or Foxo1 in SF-1 neurons results in leanness (34,52). Conversely, deletion of Pten, another negative regulator of insulin signaling, results in obesity (34), similar to the effects of SF-1 deletion of Ptpn1.…”
Section: By Unpaired T Test (A-c) or Paired T Test (D) (E) Pstatmentioning
confidence: 95%